2020
DOI: 10.1371/journal.pone.0240453
|View full text |Cite
|
Sign up to set email alerts
|

SWATH-MS based proteomic profiling of pancreatic ductal adenocarcinoma tumours reveals the interplay between the extracellular matrix and related intracellular pathways

Abstract: Pancreatic cancer accounts for 2.8% of new cancer cases worldwide and is projected to become the second leading cause of cancer-related deaths by 2030. Patients of African ancestry appear to be at an increased risk for pancreatic ductal adenocarcinoma (PDAC), with more severe disease and outcomes. The purpose of this study was to map the proteomic and genomic landscape of a cohort of PDAC patients of African ancestry. Thirty tissues (15 tumours and 15 normal adjacent tissues) were obtained from consenting Sout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“… 64 Quantitative proteomics is increasingly adopted for identifying biomarkers of early pancreatic cancer, such as actinin-4, annexin A2, Bcl-2, H1.3, IGFBP2, IGFBP3, and galectin-1 ( Figure 5 ). 65 , 66 , 67 , 68 , 69 , 70 , 71
Figure 5 Quantitative proteomics adopted in the discovery of various cancer biomarkers Many biomarkers for different types of cancer are identified through quantitative proteomics. Biomarkers were found from cancer tissue (black), plasma/serum (orange), and exosome (green).
…”
Section: Identifying Potential Biomarkers With Quantitative Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 64 Quantitative proteomics is increasingly adopted for identifying biomarkers of early pancreatic cancer, such as actinin-4, annexin A2, Bcl-2, H1.3, IGFBP2, IGFBP3, and galectin-1 ( Figure 5 ). 65 , 66 , 67 , 68 , 69 , 70 , 71
Figure 5 Quantitative proteomics adopted in the discovery of various cancer biomarkers Many biomarkers for different types of cancer are identified through quantitative proteomics. Biomarkers were found from cancer tissue (black), plasma/serum (orange), and exosome (green).
…”
Section: Identifying Potential Biomarkers With Quantitative Proteomicsmentioning
confidence: 99%
“…Quantitative proteomics is a promising tool for revealing the molecular mechanisms of drug action. 58 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 Proteomics drug maps have greatly promoted the discovery of drug targets. After the quantitative analysis for 10,000 proteins and 55,000 phosphorylation sites (p-sites) from 125 cancer cell lines, the proteome activity landscapes were obtained.…”
Section: Discovering Drug Targets With Quantitative Proteomicsmentioning
confidence: 99%
“…In PC, the dense TME architecture ensures that drug delivery is impeded. Our group recently showed using SWATH-MS, the intricate network of signaling pathways within the ECM of PC tumors highlighting different known and potentially novel associating proteins ( 27 ). Furthermore, mouse models of PC showed that CAFs accumulate gemcitabine and this may contribute to drug resistance ( 28 ).…”
Section: Chemoresistance In Pdac: Role Of the Tumor Microenvironmentmentioning
confidence: 99%
“…Sequential window of all theoretical mass spectra (SWATH-MS), a type of data-independent acquisition (DIA) LC–MS technique, also allows for reproducible analysis of prepared peptides in a systematic and unbiased manner [ 25 , 26 ]. Several studies, such as the one recently conducted by our group, have demonstrated the utility of SWATH-MS in proteomic profiling in a solid tumour for the identification of potential biomarkers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%